Digital Capabilities as An Effort to Increase Competitive Advantage and Firm Survival in Micro Businesses - Maulana, Yogi Sugiarto; Hadiani, Dian; Nurjanah, Siti (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
One of the main weaknesses of microbusinesses in surviving the crisis is their inability to adapt and their lack of resources. Knowledge and skills are essential resources for increasing competitive advantage. For this reason, this study aims to analyze the influence of digital capability on competitive advantage and its impact on firm survival in micro businesses. The research method used is a survey research method. The respondents in this study amounted to 108 microbusiness owners in Ciamis Regency. The data obtained was analyzed using the structural equation model (SEM) with the help of SmartPLS software version 3.2.9. The study results show that digital capability positively and significantly affects competitive advantage and firm survival. In addition, competitive advantage positively and substantially affects firm survival. A competitive advantage can also mediate the influence of digital capabilities on firm survival positively and significantly. We found that digital capabilities, rather than business capabilities, influence firm survival more. Therefore, microbusiness actors are advised to increase their knowledge and skills through training and strategic cooperation. These results support the resource-based view (RBV) theory, which has proven relevant and can be used in microbusiness.